Stains on My Name, War in My Veins : Guyana and the Politics of Cultural Struggle - Williams, Brackette F. (Book collections on Project MUSE., 1991)
Burdened with a heritage of both Spanish and British colonization and imperialism, Guyana is today caught between its colonial past, its efforts to achieve the consciousness of nationhood, and the need of its diverse subgroups to maintain their own identity. Stains on My Name, War in My Veins chronicles the complex struggles of the citizens of Guyana to form a unified national culture against the pulls of ethnic, religious, and class identities. Drawing on oral histories and a close study of daily life in rural Guyana, Brackette E. Williams examines how and why individuals and groups in their q.